PENGARUH TEKNIK PENYUNTIKAN INTRAVENA DENGAN CARA MENGALIRKAN ALIRAN INFUS TERHADAP KEJADIAN FLEBITIS DI RUANG PERAWATAN BOUGENVILE RSUD TOBELO - Seleky, Wanti; Kumaat, Lucky T; Mulyadi, Ns (Universitas Sam Ratulangi, 2016)
Abstract.Nosocomial infections that most common in hospitals is phlebitis, inflammation of a vein due to infusion. This research purposes are known effects of intravenous injection technique by flowing streams infusion on the incidence of phlebitis in cast care hospital BougenvileTobelo.The research sample is 30 respondents who attached a drip to the control group and the intervention group.Design researchis using research methods Pre-Experiments with Static-group approach Comparison.Results of research is using Mann Whitney Test Value P value of 0.001 <0.05.So the value of P Value